Diagnostic implications of associated defects in patients with typical orofacial clefts - Isabella L. Monlleó; Amanda G.R. de Barros; Marshall I.B. Fontes; Ana K.M. de Andrade; Gisele de M. Brito; Diogo L.L. do Nascimento; Vera L. Gil- (Elsevier, 2015)
Objectives: To describe prevalence of associated defects and clinical-genetic characteristics of patients with typical orofacial clefts seen at a reference genetic service. Methods: Descriptive study conducted between September of 2009 and July of 2014. Two experienced dysmorphologists personally collected and coded clinical data using a validated, standard multicenter protocol. Syndromic cases were defined by the presence of four or more minor defects, one or more major defects, or recognition of a specific syndrome. Fisher's exact and Kruskal-Wallis tests were used for statistics. Results: Among 141 subjects, associated defects were found in 133 (93%), and 84 (59.5%) were assigned as syndromic. Cleft palate was statistically associated with a greater number of minor defects (p < 0.0012) and syndromic assignment (p < 0.001). Syndromic group was associated with low birth weight (p < 0.04) and less access to surgical treatment (p < 0.002). There was no statistical difference between syndromic and non-syndromic groups regarding gender (p < 0.55), maternal age of 35 years and above (p < 0.50), alcohol (p < 0.50) and tobacco consumption (p < 0.11), consanguinity (p < 0.59), recurrence (p < 0.08), average number of pregnancies (p < 0.32), and offspring (p < 0.35). Conclusions: There is a lack of information on syndromic clefts. The classification system for phenotype assignment adopted in this study has facilitated recognition of high prevalence of associated defects and syndromic cases. This system may be a useful strategy to gather homogeneous samples, to elect appropriate technologies for etiologic and genotype-phenotype approaches, and to assist with multiprofessional care and genetic counseling. Resumo: Objetivos: descrever a prevalência de defeitos associados e as características genético-clínicas de pacientes com fendas orofaciais típicas (FOT) em um serviço de referência em genética. Métodos: Estudo descritivo realizado entre setembro/2009 a julho/2014. Os dados foram colhidos e codificados por dois observadores clínicos com experiência em dismorfologia, utilizando protocolo validado em estudo multicêntrico. Presença de 4 ou mais defeitos minor, um ou mais defeitos major e diagnóstico de síndrome reconhecida foram critérios utilizados para classificar o caso como sindrômico. Utilizou-se Teste Exato de Fisher para análise de variáveis categóricas e Kruskal-Wallis para igualdade de médias. Resultados: Entre 141 sujeitos, 133 (93%) apresentavam ao menos um defeito minor ou major associado, sendo 84 (59,5%) classificados como sindrômicos. As fendas de palato estiveram associadas com maior número de defeitos minor (p < 0,0012) e com a classificação sindrômica (p < 0,01). O grupo sindrômico apresentou maior taxa de baixo peso (p < 0,04) e menor acesso a tratamento cirúrgico (p < 0,02). Não houve diferenças entre os grupos quanto ao gênero (p < 0,55), idade materna ≥ 35 anos (p < 0,50), ingestão de álcool (p < 0,50) e tabagismo (p < 0,11), consanguinidade (p < 0,59), recorrência familial (p < 0,08) e média de gestações (p < 0,32) e de filhos nascidos vivos (p < 0,35). Conclusões: Existe escassez de informações sobre fendas sindrômicas. O método de classificação fenotípica utilizado possibilitou a identificação de alta prevalência de defeitos associados e de casos sindrômicos. Este método seria uma alternativa para homogeneizar amostras, determinar tecnologias visando investigação etiológica e estudos de correlação genótipo-fenótipo, além de colaborar para intervenção multiprofissional e aconselhamento genético. Keywords: Cleft lip, Cleft palate, Congenital abnormalities, Phenotype, Palavras-chave: Fenda de lábio, Fenda de palato, Anomalias Congênitas, Fenótipo